2017
DOI: 10.1021/acs.inorgchem.7b01369
|View full text |Cite
|
Sign up to set email alerts
|

Selective Double Hydroboration and Dihydroborylsilylation of Organonitriles by an Iron–indium Cooperative Catalytic System

Abstract: Organonitriles (RC≡N) were selectively converted into the corresponding diborylamines (RCHN(Bpin)) in reactions with pinacolborane (pinBH) in the presence of a catalytic amount of the iron-indium complex [Fe(CHCN)][cis-Fe(CO)(InCl)]. The catalytic reaction mechanism was tentatively proposed. In addition, this catalytic system was found to be applicable for the synthesis of borylsilylamine in high yield when organonitrile was treated with hydroborane and hydrosilane simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…Although several reports in literature [41][42][43][44][45][46][47][48][49] have described the catalytic hydroboration of aryl nitriles with lower conversion to the desired diboryl amine products even after prolonged reaction times, the current protocol demonstrates that we can achieve the target compounds in very good yields under mild conditions and in shorter reaction times. To extend the synthetic scope of this response, we also tested the chemoselective hydroboration of nitriles.…”
Section: Entry 3 L)mentioning
confidence: 74%
See 1 more Smart Citation
“…Although several reports in literature [41][42][43][44][45][46][47][48][49] have described the catalytic hydroboration of aryl nitriles with lower conversion to the desired diboryl amine products even after prolonged reaction times, the current protocol demonstrates that we can achieve the target compounds in very good yields under mild conditions and in shorter reaction times. To extend the synthetic scope of this response, we also tested the chemoselective hydroboration of nitriles.…”
Section: Entry 3 L)mentioning
confidence: 74%
“…[36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine. [40] Recently, Nakazawa et al reported the use of an ironindium complex as a catalyst for the hydroboration of aryl and alkyl nitriles, [41] while Nikonov et al introduced the Mo(IV) complex as a catalyst (5 mol %), which resulted in the hydroboration of acetonitrile and benzonitrile using the only catecholborane. [42][43] The Szymczak working group and Gunanathan et al have also reported that a ruthenium metal-based complex (1 mol %) catalyzed nitrile and imine hydroboration in preparing the corresponding diborylamines.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] During the last decade, since the discovery of Mo-catalyzed dihydroboration of nitriles, [19,20] a number of research publications concerning other catalytic systems have appeared in the literature, with the vast majority of developments being accomplished in the area of transition metal catalysis. The newly developed methods mostly rely on Ru [22,29,30] and Co [21,23,31,32] catalysts, with a handful of examples using Ti, [33,34] Mn, [35] Fe [36] and Ni. [37] With regards to f-block elements, only two reports on using Er, Y, Dy, Gd [38] and Th [39] systems in dihydroboration of nitriles have been disclosed.…”
Section: Transition Metal Catalysts 21 Early Attempts: Mo-catalyzedmentioning
confidence: 99%
“…Moving beyond ruthenium systems, a series of abundant base metal catalysts (Fe, [36] Co, [21,23,31,32] Ni [37] and Mn [35] ) have been reported to facilitate hydroboration of nitriles. Thus, ironcatalyzed reactions were disclosed by Nakazawa et.…”
Section: Late D-block Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation